A simple culture system for time-lapse video recording of bovine embryos - Peippo, Jaana; Bredbacka, Peter (Agricultural and Food Science, 1996)
Continuous observation of embryonic growth can improve understanding of the early developmental events and allow us to use parametric statistical analyses with time as a parameter. A cinematographic study such as that reported here utilizes time-lapse video recording. Previously published methods for time-lapse video recording have involved building an incubator around a microscope, a process that is both expensive and laborious. Here we present a simplified method for time-lapse video recording of early bovine embryo development. The embryos were cultured during a 24-hour period in a standard pregassed tissue culture bottle, which was darkened and placed on the heating stage of an inverted microscope for recording through a red filter. The control embryos were cultured in a conventional CO2 incubator. After 10 replicates we could not find a statistically significant difference between the cell numbers of these two treatments (P=0.95), suggesting that the culture setup is appropriate for continuous observation of early cleavage of the cattle embryo.